2012
DOI: 10.1029/2011jc007753
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of trends in extreme value wave height and wind speed

Abstract: [1] Global altimeter data spanning a period of more than 20 years is analyzed to determine whether there are measurable trends in extreme value return period estimates of wind speed and wave height. The data is subdivided into sections of 4 years duration and extreme value analysis applied to each section. The trends in values across these sections indicate that there appears to be a positive trend in 100 year return period values of wind speed but no consistent trends for 100 year return period wave height. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 69 publications
7
98
2
2
Order By: Relevance
“…By modulating interactions between oceans and the atmosphere waves play an important role in the climate system [Hemer et al, 2012] and are likely to be affected by global warming. In several regions of the world, wave heights show already an upward trend in recent decades, especially the extremes [Wang et al, 2009;Young et al, 2011Young et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…By modulating interactions between oceans and the atmosphere waves play an important role in the climate system [Hemer et al, 2012] and are likely to be affected by global warming. In several regions of the world, wave heights show already an upward trend in recent decades, especially the extremes [Wang et al, 2009;Young et al, 2011Young et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The study of wave extremes by using altimeter data has proved to be very reliable and useful (Zieger et al, 2009;Vinoth and Young, 2011;Young et al, 2011Young et al, , 2012. However, the most severe limitation of satellite altimeter data is the sampling rate and the temporal and spatial sparseness .…”
Section: Validated Swh Modeled Results Inmentioning
confidence: 99%
“…In this respect, Young et al (2012) states that the higher SWH found in 5 the sub-tropical region of the South Atlantic is associated to swell generated by storms in the Southern Ocean. and 6b in Chen et al (2004)).…”
mentioning
confidence: 99%
“…The rate of increase is greater for extreme events as compared to the mean condition. This database was then use to evaluate extreme values of wave height and wind speed (Young et al, 2012). Within this study, a methodology was developed for obtaining trends based on short (4-year) segments of the altimeter records.…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%